Pelatihan Pembuatan Akuarium sebagai Upaya Peningkatan Keterampilan dan Kesadaran Ekologis Mahasiswa Institut Teknologi Kelautan Buton - La Suriadi; Meliyanti Thamrin; Suhartin; Ananta Wira Pratama; Fadli Insani Ihsan (Universitas Mataram, 2025)
Abstract: This community service activity aims to enhance the skills of students from the Institute of Marine Technology Buton (ITKB) in aquarium construction and to instill ecological awareness. The training involves six lecturers with expertise in aquaculture, biotechnology, and fisheries, and is conducted on January 17, 2025, at the ITKB campus. Participants consist of students interested in aquariums as a medium for education, aesthetics, and business opportunities. The training material includes techniques for selecting materials, assembling aquariums, and applying environmentally friendly aquarium concepts based on aquaponic systems. Evaluation results show a significant improvement in students' technical skills in aquarium construction, awareness of the importance of maintaining aquatic ecosystems, and their understanding of aquarium-based business opportunities. Additionally, this training encourages student innovation in sustainable aquarium design. This program is expected to contribute to enhancing students' competencies and supporting the development of ecology-based fisheries industries.